2021
DOI: 10.1017/gmh.2021.8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health integration in primary health services after the earthquake in Nepal: a mixed-methods program evaluation

Abstract: Background In the aftermath of the devastating 2015 earthquakes in Nepal, three non-governmental organizations collaborated to develop a program responding to the immediate mental health and psychosocial support (MHPSS) needs in three severely affected districts: Dhading, Gorkha, and Sindhuli. The program was implemented between April 2015 and February 2017 and aimed to (i) strengthen health worker capacity to provide integrated MHPSS services; and (ii) increase access to mental health services. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Curricula content was mostly focused on disease and disaster management. Some content was about personal safety and security [ 49 , 50 , 55 , 204 – 206 , 208 , 209 ], waste management [ 66 , 212 , 299 ], mental health [ 95 , 105 , 166 , 172 , 177 , 213 , 221 , 235 , 259 , 277 , 293 ], infection control and prevention [ 139 , 168 , 241 , 264 , 302 ], pest control [ 65 , 66 , 70 , 212 , 216 , 299 ], triage [ 16 , 62 , 91 , 94 , 207 , 271 , 290 ] and stress management [ 31 , 182 , 270 ]. A smaller number of curricula included surgical training [ 98 , 99 , 165 , 323 ], time management [ 223 ], stigma [ 269 ], language and local culture [ 20 ], humanitarian law and leadership [ 102 ], chemical incidents […”
Section: Resultsmentioning
confidence: 99%
“…Curricula content was mostly focused on disease and disaster management. Some content was about personal safety and security [ 49 , 50 , 55 , 204 – 206 , 208 , 209 ], waste management [ 66 , 212 , 299 ], mental health [ 95 , 105 , 166 , 172 , 177 , 213 , 221 , 235 , 259 , 277 , 293 ], infection control and prevention [ 139 , 168 , 241 , 264 , 302 ], pest control [ 65 , 66 , 70 , 212 , 216 , 299 ], triage [ 16 , 62 , 91 , 94 , 207 , 271 , 290 ] and stress management [ 31 , 182 , 270 ]. A smaller number of curricula included surgical training [ 98 , 99 , 165 , 323 ], time management [ 223 ], stigma [ 269 ], language and local culture [ 20 ], humanitarian law and leadership [ 102 ], chemical incidents […”
Section: Resultsmentioning
confidence: 99%
“…Other cultures may place more emphasis on family involvement in mental health and psychosocial services, requiring different items to assess the competence of including family members. This was the case original ENACT where experiences in Nepal, Uganda, and Liberia found that family members were often included in sessions (Kohrt et al, 2018;Jordans et al, 2021;Leichner et al, 2021). In South Africa, the benefits of family ⃝ 0 NOT ASSESSED = this factor was not assessed because it was not applicable or because it did not emerge in the session.…”
Section: Discussionmentioning
confidence: 99%
“…The tool, EN hancing A ssessment of C ommon T herapeutic factors (ENACT) (Kohrt et al ., 2015b ), measures a set of identified common factors: those therapeutic competencies and skills thought to be required for a counsellor to adequately deliver any EBI effectively. This tool was initially piloted in Nepal, Liberia, and Uganda (Kohrt et al ., 2018 ; Jordans et al ., 2021 ; Leichner et al ., 2021 ). The ENACT has undergone a robust development process in low resource settings and has shown its utility in assessing the delivery of task-shared EBIs (Kohrt et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the articles were descriptive studies on experiences in different countries(12-176), followed by before-after studies (169,173,. Also, we found 19 randomized controlled trials(261-279), 14 cross-sectional studies (280)(281)(282)(283)(284)(285)(286)(287)(288)(289)(290)(291)(292)(293), 12 observational studies(294-305), 7 reviews(306-312), 5 qualitative studies(313-317) and 3 opinion pieces (318)(319)(320). (Table 4 Supplementary material)…”
Section: Overview Of Study Characteristicsmentioning
confidence: 98%